Management of Inpatient Medical Records at Dr. Tajuddin Chalid Hospital Makassar - Julita, Ema; Suminar, Saka; Rusli, Rusli; Prabu Aji, Sulistyani; Resti Wijayanti, Fitria Eka; Prastyo, Eko; Syafri, Muhammad (International Journal of Health Sciences, 2023)
Hospitals are health care institutions that organize comprehensive individual health services that provide inpatient, outpatient, and emergency services. Therefore, hospitals are expected to be able to carry out good medical recording activities. Since pre-independence Indonesia has carried out medical recording activities, it's just that it has not been implemented properly, in terms of structuring and processing or following the correct information system. One of the supports for improving the quality of the hospital is in its Medical Record activities. Medical records are related to recording, processing data, and reporting information needed for hospital activities. Medical records as patient health records are useful for providing information from various data on activities carried out to patients while patients are undergoing treatment at the hospital. This study aims to determine how the processing of inpatient medical record files at Ujung Pandang Dr. Tajuddin Chalik Hospital. The research conducted used qualitative research methods with a descriptive approach, namely research that describes and describes the inpatient medical record management system at Dr. Tajuddin Chalik General Hospital. The results of this study are the process of processing medical record files consisting of the process of Completeness (Assembling), Coding (Coding), and Storage (Filling). Conclusion Based on the results of research on the Inpatient Medical Record Management System at Dr Tajuddin Chalid Hospital Makassar that for the input component, namely the medical record personnel of Dr Tajuddin Chalid Hospital Makassar still lacks officers so that it is no longer in accordance with the workload. For facilities and infrastructure, there is a shortage of storage shelves and expansion is needed for medical record storage rooms.